Godność człowieka a ubezwłasnowolnienie seniora - Kołodziej, Marcin (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
In the Polish legal system, human dignity is the limiting value in applying all norms. Dignity is intrinsic and inalienable. Therefore, respecting and protecting human dignity are considered fundamental duties of public authorities. At the same time, Polish legislation features an institution of incapacitation, which is among the most severe forms of legal interference in the sphere of fundamental human rights. Taking in a broader, philosophical-theological-legal perspective, this article seeks to juxtapose human dignity as a constitutional value against the institution of incapacitation concerning senior citizens. Even if necessity sometimes requires that institution of incapacitation be used, the value of human dignity should be taken into account when assessing the admissibility and lawfulness of its use in particular cases.